Mass Spectrometric Investigation of the aging processes of ballpoint ink for the examination of questioned documents - Weyermann, Céline; Justus Liebig University Giessen (My University, 2005)
In the forensic examination of documents the legitimacy of the age of an ink entry is often an essential question. Since its beginnings, the forensic questioned document field is concerned with the dating of inks. Inks aging processes follow complex paths and disagreements about the feasibility of actual methods raised worldwide among the scientific community. This controversy has been the starting point of the present work. Ball-point ink contains three main classes of compounds: solvents (50%), dyes (25%) and resins (25%). After the ink is deposited on paper, its composition begins to change qualitatively and quantitatively. While the dyes fade mainly through photochemistry processes, the aging behaviour of solvents are characterised by diffusion and evaporation processes. The aims were to actually study the aging processes of dyes and solvents found in ballpoint pens by modern mass spectrometric method in order to evaluate the potentiality and limitations of dynamic dating methods. Two major methods, Laser Desorption Ionisation - Mass Spectrometry (LDI-MS) for dyes and Gas Chromatography / Mass Spectrometry (GC/MS) for solvents were developed for this purpose and validated. The aging processes of reference substances were studied under defined storage conditions (light, heat, humidity). The same processes were investigated for the ballpoint dyes and solvents on the paper matrix. Therefore ballpoint ink strokes were exposed during several months to daylight and compared to strokes stored in the dark. On the one hand, small pieces of paper were cut, glued to a metallic sample holder with a carbon tape, and introduced into the ionisation chamber for direct analysis by LDI-MS. On the other hand, ink strokes were cut from the paper and extracted for subsequent GC/MS analysis. Moreover scanning microprobe LDI-MS was tested to microscopically visualize concentration profiles of ink dyes on the paper surface, i.e. it provides images of the chemical compound distribution. The determination of the writing sequence of crossing strokes was evaluated for questioned document expertises. Many factors influencing the fading of dye and the drying of solvents over time have been identified, to some extent evaluated. They can be divided in two mains categories: ballpoint ink composition and storage conditions of the document. Precise knowledge of these variables and their influence are necessary to deliver a scientific determination of the age of an ink entry. This work intend to give forensic scientists a better understanding of the complexity of the processes involved in the aging of a ballpoint ink matrix on a porous substrate such as paper. An overview of the ink dating issues is needed to comprehend how a dating method should be developed and validated in order to provide useful and accurate results. This has not been documented so far. Guidelines are proposed to compensate the limitations and set up valid ink dating methods. Any established dating method based on the fading of dyes or the drying of solvent has to be checked for reliability through indications of reproducibility, valid answers through blind testing and measurements errors lower than predictable variations.

In den forensischen Wissenschaften ist die Bestimmung des Alters einer Kugelschreibereintragung (z.B. Kugelschreiberstrich) ein wichtiges Kriterium bei der Echtheitsprüfung von Dokumenten. Seit Beginn dieser Untersuchungen ist die Altersbestimmung eine wichtige und meist unbeantwortet Frage geblieben. Die forensischen Wissenschaftler streiten sich über die Möglichkeit und die Validierung von Datierungsmethoden. Diese Kontroverse ist der Angangspunkt dieser Arbeit gewesen. Kugelschreiberpasten bestehen aus drei Hauptkomponenten: Lösungsmitteln (50%), Farbstoffen (25%) und Harzen (25%). Nach dem Auftragen der Pasten auf Papier findet mit der Zeit eine qualitative und quantitative Veränderung der Zusammensetzung der Kugelschreibereintragung statt. Während Farbstoffe ausbleichen, d.h. vor allem photochemisch abgebaut werden, wird das Alterungsverhalten der Lösungsmittel durch den Verdampfungs- und Diffusionsprozess charakterisiert. In der vorgestellten Arbeit, sind die Alterungsprozesse von Farbstoffen und Lösungsmitteln mittels moderner massenspektrometrischen Methoden und deren möglichen Anwendung zur Altersbestimmung von Kugelschreibertinte untersucht worden. Zwei Hauptmethoden, Laser-Desorptions-/Ionisations-Massenspektrometrie (LDI-MS) für die Farbstoffen und Gas-Chromatographie-Massenspektrometrie (GC/MS) für die Lösungsmittel, sind für diesen Zweck methodisch weiterentwickelt und validiert worden. Die Alterungsprozesse von Referenzsubstanzen sind unter verschiedenen Bedingungen (Licht, Hitze, Feuchtigkeit) untersucht worden. Dieselben Prozesse sind dann für die Farbstoffen und Lösungsmittel auf der Papiermatrix verfolgt worden. Dazu wurden über mehrere Monate hinweg Eintragungen von mehreren Kugelschreibern dem normalen Sonnenlicht ausgesetzt und mit im Dunkeln gelagerten Proben verglichen. Dafür wurden einerseits kleine Stücke aus dem Papier ausgeschnitten und auf einem Probenteller befestigt, um dann LDI-MS Messungen direkt von den Tinten auf dem Papier durchzuführen. Andererseits wurden Kugelschreiberstriche für die GC-MS-Analyse aus dem Papier ausgeschnitten und anschließend extrahiert. Außerdem ist Ortaufgelöste LDI-MS getestet worden um die räumliche chemische Verteilung von Tinte auf dem Papier zu bestimmen. Die Reihenfolge zweier sich kreuzender Tintenlinien konnte auf diese Weise zur Echtheitsbestimmung des Dokumentes untersucht werden. Die Ergebnisse über Alterungsverhalten von Farbstoffen und Strichen von Kugelschreibern während einiger Jahre haben viele Faktoren offengelegt, die den Alterungsprozess beeinflussen. Zwei Hauptgruppen sind identifiziert worden: Die ursprüngliche Zusammensetzung der verwendeten Kugelschreiberpaste und die Lagerungsbedingungen des Dokumentes. Es ergibt eine umfangreiche, fundamentale und weitreichend nutzbare Studie der Alterung von Tinte, die bisher nicht existierte. Die Ergebnisse zeigen ausserdem auf welche Probleme ein Gutachter sto& #946;en wird, wenn er eine Altersbestimmung durchführen will. Eine Strategie zur Entwicklung von Datierungsmethoden ist am Ende dieser Arbeit vorgeschlagen. Zuerst sollte eine ausführlische Tintendatenbank aufgebaut werden und zur Verfügung stehen. Gute und detaillierte Kenntiss der Alterungsprozesse aller vorkommenden Komponenten ist erforderlisch. Dazu dient die vorgestellte Arbeit als eine wissenschaftlische und protokollarische Vorgabe. Weitere Werte für bestimmte Alterungsparameter müssen trotzdem bestimmt werden, um eine mögliche Applikation zu entwicklen. Als letzter Schritt muss jede Methode zur Altersbestimmung unbedingt validiert werden.
Massenspektrometrische Untersuchung der Alterungsprozesse von Kugelschreibertinte für die Echtheitsprüfung von Dokumenten
Keywords: Kriminalistik; Massenspektrometrie; Farbstoff; Lösungsmittel; Forensic Mass Spectrometry; Dye; Solvent; ddc:540